Effects of nitrogenous wastes on survival of the Barton Springs salamander (Eurycea sosorum). (28th July 2017) - Crow, Justin C.; Ostrand, Kenneth G.; Forstner, Michael R.J.; Catalano, Matthew; Tomasso, Joseph R.
Abstract: The objective of our study was to determine the acute toxicity of 3 common aquatic nitrogenous toxicants to the federally endangered Barton Springs salamander ( Eurycea sosorum ). Based on our findings, the 96‐h median lethal concentrations (96‐h LC50) for un‐ionized ammonia‐N, nitrite‐N, and nitrate‐N to E. sosorum are 2.0 ± 0.32, 31.7 ± 4.02, and 968.5 ± 150.6 mg/L, respectively. These results establish a benchmark for the tolerance of plethodontid salamanders to these toxicants and indicate that current water quality criteria are adequate for their protection. Environ Toxicol Chem 2017;36:3003–3007. © 2017 SETAC